Napoleon a life - Roberts, Andrew 1963- (Viking, 2014)
" ... the first single-volume, cradle-to-grave biography to take advantage of the recent publication of Napoleon's thirty-three thousand letters, which radically transform our understanding of his character and motivation"...Jacket
Includes bibliographical references (pages 859-888) and index
Keywords: Napoleon / I / Emperor of the French / 1769-1821; Napoleon -- I, -- Emperor of the French, -- 1769-1821; Napoleon; Napoleon -- I. -- Frankreich, Kaiser -- 1769-1821; 1789 - 1815; Geschichte 1789-1815; Biography; Emperors; Geschichte; Emperors -- France -- Biography; France; Frankreich; France -- History -- 1789-1815; 1789 - 1815 -- fast; Biografie